Sonication culture improves microbiological diagnosis of modular megaprostheses. Issue 7 (19th September 2016) - Puchner, Stephan E.; Döring, Kevin; Staats, Kevin; Böhler, Christoph; Lass, Richard; Hirschl, Alexander M.; Presterl, Elisabeth; Windhager, Reinhard; Holinka, Johannes
ABSTRACT: Modular megaprostheses are known for high infection rates followed by high rates of revisions. Microbial biofilms growing adherently on prosthetic surfaces may inhibit the detection of the pathogens causing prosthetic joint infections. We sought to answer the following questions: Does sonication culture (SC) improve the microbiological diagnosis of periprosthetic infections of megaprostheses compared to conventional tissue culture (TC)? Which pathogens were detected on the surface of megaprostheses with either SC or TC and do the findings help to identify low‐grade infections? Included were 31 patients with modular megaprostheses, whose implant had been explanted due to suspected joint infection or revision surgery. SCs were performed according to the protocol by Trampuz et al. The diagnosis of infection was evaluated according to the definition of the Musculoskeletal Infection Society. The sensitivity of SC was 91.3% compared to 52.2% for TC and the specificity was 100% for SC and TC ( p  = 0.004). Under preoperative antibiotic therapy, the sensitivity of SC was 83.3% while the sensitivity of TC was 50%. Without preoperative antibiotic therapy the sensitivity of SC was 100% compared to 54.5% for TC. In nine cases, SCs detected microorganisms, while TC was negative. Detected bacteria were Staphylococcus epidermidis in four, Micrococcus species in one, Finegoldia magna in one, Brevibacterium casei in one, Pseudomonas fluorescens in one, and Enterococcus faecium in one. SC is a reliable method for dislodging pathogens from orthopedic implants. The SC of modular megaprostheses showed significantly higher pathogen detection than the periprosthetic TC, especially for low virulence pathogens. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1383–1387, 2017.